Analysis of genetic structure and function of clustered regularly interspaced short palindromic repeats loci in 110 Enterococcus strains - Tao, Shuan; Zhou, Dongdong; Chen, Huimin; Li, Na; Zheng, Lin; Fang, Yewei; Xu, Yao; Jiang, Qi; Liang, Wei (Frontiers in Microbiology, 2023)
Clustered regularly interspaced short palindromic repeats (CRISPR) and their CRISPR-associated proteins (Cas) are an adaptive immune system involved in specific defense against the invasion of foreign mobile genetic elements, such as plasmids and phages. This study aims to analyze the gene structure of this system in the Enterococcus genome and to explore the function of the CRISPR system in Enterococcus, especially in regard to drug resistance. The whole genome information of 110 enterococci was downloaded from the NCBI database to analyze the distribution and the structure of the CRISPR-Cas system including the Cas gene, repeat sequences, and spacer sequence of CRISPR-Cas system by bioinformatics methods; find drug resistance-related genes and analyze the relationship between them and CRISPR-Cas system. Multilocus sequence typing (MLST) of enterococci was performed against the reference MLST database. Information on the drug resistance of Enterococcus was retrieved from the CARD database, and its relationship to the presence or absence of CRISPR was statistically analyzed. Among the 110 Enterococcus strains, 39 strains (35.45%) contained a complete CRISPR-Cas system, 87 CRISPR arrays were identified, and 62 strains contained Cas gene clusters. The CRISPR system in the Enterococcus genome was mainly type II-A (59.68%), followed by type II-C (33.87%). The phylogenetic analysis of the cas1 gene sequence was basically consistent with the typing of the CRISPR-Cas system. Of the 74 strains included in the study for MLST typing, only 19(25.68%) were related to CRISPR-Cas typing, while the majority of the strains (74.32%) of MLST typing were associated with the untyped CRISPR system. And the CRISPR-Cas system may only be related to the carrying rate of some drug-resistant genes and the drug-resistant phenotype. In conclusion, the distribution of the enterococcus CRISPR-Cas system varies greatly among different species and the presence of CRISPR loci reduces the horizontal transfer of some drug-resistance genes. Keywords: Enterococcus; gene structure; CRISPR-Cas system; drug resistance gene